A Bioversity-CIAT Alliance collaboration with the Ucayali government (Peru) promotes agroecologically supported bio trade. - Tristan, Maria Claudia; Staiger, Simone; Ivanova, Yovita (2024)
The government of Ucayali in Peru approved its Regional Strategy and 2028 Action Plan that promotes agroecologically supported bio trade. The plan advances sustainable use of native biodiversity. It strengthens the regulatory and institutional framework, improves the conditions for supplying biodiversity products, promotes research and innovation, encourages knowledge exchange, and establishes the monitoring and evaluation system for bio trade. The Alliance and Terra Nuova supported the participatory multi-stakeholder process of developing the strategy and action plan.